Elements which stimulate gene amplification in mammalian cells: role of recombinogenic sequences/structures and transcriptional activation. - McArthur, J G (1991)
HSAG-1 is a 3.4 kb mammalian genomic element which has been shown to stimulate the amplification of the pSV2DHFR expression vector in cis when transfected into a variety of cell lines (1). This amplification stimulatory activity requires the interaction of multiple positive acting elements that include sequence features associated with recombination 'hotspots', such as Alu-like repetitive sequences and A/T rich regions (2). We demonstrate here that two other members of the HSAG family of elements, HSAG-2 and HSAG-5, also stimulate vector amplification. By analysis of the HSAG-2 nucleotide sequence and of the amplification activity of HSAG-2 and HSAG-5 subfragments, we show that this activity also involves the interaction of multiple positive acting elements. The autonomous replication of the HSAG containing vectors is not responsible for this effect. We also show that the orientation of HSAG elements in pSV2DHFR has a profound effect on their amplification stimulatory activity, and present evidence that the transcription of these elements in pSV2DHFR is necessary for the effect.